MENINGKATKAN HASIL BELAJAR PJOK MATERI LARI AKSELERASI JARAK PENDEK 100 METER MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP SISWA KELAS IX-3 SMP - Hamka Hamka (Universtas Negeri Makassar, 2022)
Classroom Action Research aims to improve learning outcomes in physical, sports and health education (PJOK) for the 100-meter short distance accelerated running material through the application of the Jigsaw type cooperative learning model. The results obtained after the action was carried out in the form of cycle I obtained an average final score of 90.6 which was in the Very Good category and classical completeness reached 90.32%, then proceeded to cycle II, after actions and improvements were made to the implementation of the model. Jigsaw cooperative learning obtained an average score of 94.7 and was in the Very Good category with a percentage of 100%. The time records in each cycle became better, and all students were able to exceed the previous time records. Running Short distance acceleration of 100 meters with the fastest time achieved is 19.50 seconds for male students and 20.40 for female students. Learning is student centered (Student Centered) because it is active and students work together in achieving the learning objectives, namely understanding and being able to apply the correct 100 meter short distance acceleration running technique. In addition, students are able to achieve a better time record than the previous time achievement. From the results of the analysis, it can be concluded that by applying the jigsaw learning model, it has improved the learning outcomes of PJOK on the 100 meter short distance acceleration running material for students in class IX-3 UPTD SMP Negeri 6 Barru.